2018
DOI: 10.1088/1361-6560/aad444
|View full text |Cite
|
Sign up to set email alerts
|

Relative Patlak plot for dynamic PET parametric imaging without the need for early-time input function

Abstract: The Patlak graphical method is widely used in parametric imaging for modeling irreversible radiotracer kinetics in dynamic PET. The net influx rate of radiotracer can be determined from the slope of the Patlak plot. The implementation of the standard Patlak method requires the knowledge of full-time input function from the injection time until the scan end time, which presents a challenge for use in the clinic. This paper proposes a new relative Patlak plot method that does not require early-time input functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Based on the existing dual‐time‐point protocol already used in clinical practice, we successfully developed and validated a new approach of generating K i images from the dual‐time‐point imaging data alone. Other approaches using a 30‐min temporally continuous dynamic scan have been reported previously for K i estimation 14–17 . A vendor product of FlowMotion TM multiparametric PET has also been released commercially by Siemens for direct Patlak reconstruction 17,48,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the existing dual‐time‐point protocol already used in clinical practice, we successfully developed and validated a new approach of generating K i images from the dual‐time‐point imaging data alone. Other approaches using a 30‐min temporally continuous dynamic scan have been reported previously for K i estimation 14–17 . A vendor product of FlowMotion TM multiparametric PET has also been released commercially by Siemens for direct Patlak reconstruction 17,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…This seriously limits its clinical application. Efforts have been made to simplify the dynamic imaging protocol by acquiring a single dynamic scan, [14][15][16][17] usually starting 10-30 min post injection and ending to 55-60 min post injection, and calculating its Patlak plot 18 from which it is possible to derive K i quantification of FDG PET. To avoid sequential arterial blood sampling, studies have been reported to combine a single dynamic scan (~60-80min post injection) with a population-based input function to facilitate their subjects for each ROI is smaller than 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Then, in the plane referred to Cartesian coordinates , define the functions and by . The points give the parametric representation of a curve which is known as the standard Patlak plot [ 38 ]. Comparison with Equation ( 34 ) and the condition on show that the curve is asymptotically linear.…”
Section: Patlak and Logan Graphical Approachesmentioning
confidence: 99%
“…Comparison with Equation ( 34 ) and the condition on show that the curve is asymptotically linear. Thus the slope and the adimensional constant intercept are estimated in terms of the data by linear regression [ 38 ]. The procedure may be applied pixel-wise.…”
Section: Patlak and Logan Graphical Approachesmentioning
confidence: 99%
See 1 more Smart Citation